The study of commercial Titanium Dioxide (TiO2) Degussa P25 for the adsorption of acidic dye / Nur Shazwani Abdul Mubarak, S. Sabar and Ali H. Jawad - Abdul Mubarak,, Nur Shazwani; Sabar, S; Jawad, Ali H. (Faculty of Applied Sciences, 2020)
Commercial titanium dioxide Degussa P25 (TiO2) was used for the adsorption of reactive red 120 (RR120) dye in a batch system. The optimization functions such as solution pH (3-12), adsorbent dosage (0.02 g-1.2 g), and initial dye concentration (30-400 mg/L) were studied. The equilibrium adsorption data for RR120 dye was analyzed by two types of isotherm models which are Langmuir and Freundlich models. The adsorption at equilibrium showed a better fit for linear Langmuir isotherm with the adsorption capacity, qmax of 18.62 mg/g at 303 K. The adsorption kinetic was well-described by pseudosecond order model. TiO2 showed a decent outcome due to the ability to adsorb target pollutants with the added advantage of providing large hydroxyl groups (OH) on the surface of TiO2 so that pollutants can be adsorbed by interacting on the surface of OH.